Kadar Proksimat Telur Itik Pengging, Itik Tegal, Itik Magelang di Balai Pembibitan dan Budidaya Ternak Non Ruminansia (BPBTNR), Ambarawa - Tika Andriani; Muhammad Anwar Djaelani; Tyas Rini Saraswati (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2015)
Local duck native germplasm Indonesia which has the genetic quality and potential to be developed as a prolific egg producer. Each type has a different chemical composition duck on her eggs. This study aims to transform and analyze proximate Pengging duck eggs, Tegal duck, and Magelang ducks that includes protein, fat, water, ash and carbohydrates. Egg samples were taken from three different types of ducks, namely: Magelang ducks, Tegal duck and Pengging duck six months old to be tested proksimatnya levels. This study consisted of 3 treatments and 6 repetitions on each type of duck eggs. Data were analyzed using analysis of variance (ANOVA), followed by a further test using the Least Significant Differences (LSD) at 95% confidence level. The results showed that levels of the protein and no significant water on three types of duck eggs, while the levels of fat, ash and carbohydrates showed significantly different results. It can be concluded that the difference in levels proximate duck eggs from Magelang ducks, Tegal ducks and Pengging ducks revealed that there is a difference of potential metabolites of the three types of ducks.Keywords: Duck Egg, Proximate, Least Significant Differences